Administrative costs of environmental taxes in the Czech Republic - Lenka Hyklová (European Financial and Accounting Journal, 2017)
Administrative costs of environmental taxes are a more and more discussed topic. These costs should be understood as part of the tax entity, so by the tax administrator. The aim of this thesis is to evaluate the administrative costs of environmental taxes in the Czech Republic from the perspective of the tax administrator. These costs are analyzed by customs offices, Ministry of Finance, General Directorate. In the Czech Republic there are no statistics to this problem, that before was for research interviewing form. In this paper there excise taxes and environmental taxes are compared with an emphasis on administrative costs of these taxes. The effectiveness of both taxes are compared. The effectiveness of environmental taxes is not as high as the effectiveness of excise taxes.
Keywords: H23; 650; Administrative costs; Environmental taxes; Excise taxes